STEEL DRUMS IN ZAMBIA (International Library of African Music, 1969)
During a recent visit to Zambia of one of the top Trinidadian Steel bands, the "Gay Desperadoes”, their tuner, Wallace Austin, made and tuned no less than 43 'pans' from local oil drums, in the six pitches now current in Trinidad-tenor, double-tenor, alto, guitar, tenor-bass and bass.
Keywords: Musical instruments; Drum; African Music; Zambia; Steel Drum (Instrument)